A CASE STUDY ON THE PESTALOZZI ASSOCIATION OF SENADOR CANEDO - GO FROM THE PERSPECTIVE OF ACCESSIBILITY FOR PEOPLE WITH DISABILITIES - Souza, Eliane de Franà§a; Chaves, Thiago Alcides de Lima; Oliveira, Bethy Hogla Rodrigues Marques (CIPEEX, 2022)
IT IS UNDERSTOOD THAT PESTALOZZI INSTITUTE GUARANTEES THE QUALITY OF LIFE OF PEOPLE WITH SPECIAL NEEDS THROUGH THE ARTICULATION OF ACTIONS IN DEFENSE OF THEIR RIGHTS AND THE CONSTRUCTION OF THEIR CITIZENSHIP. HOWEVER, SINCE IT IS A PHILANTHROPIC INSTITUTION, NOT ALL INSTITUTIONS HAVE SUFFICIENT RESOURCES TO GUARANTEE THE QUALITY OF CARE FOR THEIR STUDENTS AND PATIENTS. JOHANN HEINRICH PESTALOZZI (1746-1827) WAS A GREAT SWISS EDUCATOR WHO DEDICATED HIS LIFE TO NEEDY CHILDREN AND THE APPRECIATION OF THE HUMAN BEING. CONSIDERED BY MANY THE GREATEST PHILOSOPHER OF MANKIND, HE INNOVATED THE PEDAGOGY OF HIS TIME, INFLUENCING SPECIAL EDUCATION. INFLUENCED BY PESTALOZZI'S WORK, THIAGO M. WURT, BORN IN GERMANY, CAME TO BRAZIL IN 1918 AND FOUNDED THE FIRST SCHOOL IN THE COUNTRY, THE PESTALOZZI INSTITUTE, IN CANOAS, RIO GRANDE DO SUL. ALSO UNDER THE SAME INFLUENCE, HELENA ANTIPOFF, FOUNDED IN 1932, THE PESTALOZZI ASSOCIATION OF BELO HORIZONTE. SINCE THEN, EDUCATORS ENCHANTED WITH THE PESTALOZZI PHILOSOPHY, HAVE FOUNDED IN ALL THE COUNTRY PESTALOZZI ASSOCIATIONS. THESE ENTITIES ARE AFFILIATED TO THE NATIONAL FEDERATION OF PESTALOZZI ASSOCIATIONS - FENASP, WHOSE MISSION IS "TO GUARANTEE THE QUALITY OF LIFE OF PEOPLE WITH SPECIAL NEEDS THROUGH THE ARTICULATION OF ACTIONS IN DEFENSE OF THEIR RIGHTS AND THE CONSTRUCTION OF THEIR CITIZENSHIP". THE ASSOCIATION PESTALOZZI OF SENADOR CANEDO IS A PHILANTHROPIC, NON-PROFIT INSTITUTION, WHOSE MISSION IS TO ACT IN DEFENSE OF THE RIGHTS OF DISABLED AND NEEDY PEOPLE THROUGH JOINT ACTIONS WITH THE GOVERNMENT, COMPANIES AND SOCIETY, IN ORDER TO IMPROVE THEIR QUALITY OF LIFE, DEVELOPING THEIR POTENTIALITIES AND MAKING THEM USEFUL TO THEMSELVES AND TO SOCIETY. IN THIS SENSE, THE PRESENT WORK HAS AS ITS GENERAL OBJECTIVE TO ANALYZE WHETHER THE PESTALOZZI OF THE CITY OF SENADOR CANEDO HAS SUFFICIENT RESOURCES TO ATTEND TO PEOPLE WITH DISABILITIES. A) TO IDENTIFY THE CLINICAL AND PEDAGOGICAL RESOURCES USED IN THE TREATMENT OF PEOPLE WITH DISABILITIES IN THE PESTALOZZI OF SENADOR CANEDO; B) TO DISCUSS THE CONSTITUTIONAL PROVISION ON THE RIGHT TO EDUCATION AND TREATMENT OF DISABILITY. FOR THIS PURPOSE, THE PROBLEM WAS DEFINED AS FOLLOWS: DOES THE PESTALOZZI OF SENADOR CANEDO HAVE ENOUGH CLINICAL RESOURCES TO ATTEND PEOPLE WITH DISABILITIES? WE USED AS METHOD THE DESCRIPTIVE FIELD RESEARCH, THE QUANTITATIVE RESEARCH, THE BIBLIOGRAPHICAL RESEARCH AND THE EXPLANATORY RESEARCH. THE PRESENT ANALYSIS WILL BE IMPORTANT, AS IT AIMS TO ADDRESS THE LACK OF RESOURCES NEEDED AT THE PESTALOZZI OF SENADOR CANEDO, CONSIDERING THAT THE INSTITUTION IS PHILANTHROPIC AND RELIES ON SOCIETY'S CONTRIBUTION FOR IMPROVEMENT. THUS, IT IS IMPORTANT TO ADDRESS THE PROPOSED THEME, SINCE THE RESULTS OBTAINED POINT TO THE LACK OF PEDAGOGICAL AND CLINICAL RESOURCES AT PESTALOZZI.